OPTIMIZATION OF PALM KERNEL OIL BIOCONVERSION INTO RHAMNOLIPID BY PSEUDOMONAS STUTZERI BK-AB12 MT-03 FOR THE MANUFACTURE OF RHAMNOLIPID-GRAPHENE QUANTUM DOT NANOPARTICLES (RL-GQD) - Ivan, Samuel
Rhamnolipid is a glycolipid biosurfactant that can be produced by various microorganisms. Rhamnolipid had been used in several fields, such as health, agriculture, food, and nanotechnology. Recent studies used rhamnolipid as a material to make nanoparticles, then applied as adsorbent. But the main problem of using rhamnolipid is low rhamnolipid productivity because its production cost too expensive. Previous study showed that Pseudomonas stutzeri BK-AB12 MT-03 mutant could produce rhamnolipid with good activity. Therefore, optimization was done in this research using response surface methodology (RSM) approach. In this research, rhamnolipid used as a material to make rhamnolipid-graphene quantum dot (RL-GQD) nanoparticles. Thus, the objectives for this study are (1) optimizing, producing, and characterisizing rhamnolipid that produced by Pseudomonas stutzeri BK-AB12 MT-03 mutant, (2) synthesize and characterisizing GQD, and (3) synthesize and characterisizing RL-GQD nanohybrids. This study has successfully obtain optimum condition to produce rhamnolipid from Pseudomonas stutzeri BK- AB12 MT-03 mutant with palm kernel oil concentration of 10.821%(v/v), urea concentration of 0.209%(w/v), and incubation for 22.487 hours. Rhamnolipid that produced analyzed using Fourier-Transform Infrared (FTIR) spectrophotometer. FTIR spectra shows that rhamnolipid that is produced has functional groups that related to rhamnolipid. The results of synthesis of GQD using pyrolysis of citric acid confirmed by FTIR spectrophotometer, X-ray diffraction (XRD) and irradiating under UV light. TEM image of GQD shows that GQD has spherical shape but agglomerated. RL-GQD hybrid that synthesized in this study had functional groups of GQD and rhamnolipid on FTIR spectra. This means rhamnolipid has successfully attached to GQD. TEM images of RL-GQD shows that RL-GQD had a sheet shape. Emulsification test of RL-GQD also done and proved that RL-GQD could be a potential EOR material.